Controlling Type I Error Rates in Assessing DIF for Logistic Regression Method Combined With SIBTEST Regression Correction Procedure and DIF-Free-Then-DIF Strategy. (December 2014) - Shih, Ching-Lin; Liu, Tien-Hsiang; Wang, Wen-Chung
The simultaneous item bias test (SIBTEST) method regression procedure and the differential item functioning (DIF)-free-then-DIF strategy are applied to the logistic regression (LR) method simultaneously in this study. These procedures are used to adjust the effects of matching true score on observed score and to better control the Type I error rates of the LR method in assessing DIF, respectively. The performance and the detailed procedure, including anchor length, of the newly proposed method are investigated through a series of simulation studies. The results show that the standard LR method yielded inflated Type I error rates as the percentage of DIF items or group ability differences increased, whereas the newly proposed method produced less inflated results. It controlled Type I error rates well in these conditions as the length of anchor increased. However, the usually suggested one-anchor or four-anchor rule of the DIF-free-then-DIF strategy is not long enough for methods that use the raw score as the matching variable. In general, the newly proposed method with eight anchor items yielded well-controlled Type I error rates under all study conditions, even with 40% DIF items in the test and a group ability difference equal to one standard deviation. It is recommended that both the SIBTEST correction procedure and the DIF-free-then-DIF strategy be applied to the LR method when assessing DIF.